Stress Fractures of the Foot and Ankle in Athletes. (November 2014) - Mayer, Stephanie W.; Joyner, Patrick W.; Almekinders, Louis C.; Parekh, Selene G.
Context: Stress fractures of the foot and ankle are a common problem encountered by athletes of all levels and ages. These injuries can be difficult to diagnose and may be initially evaluated by all levels of medical personnel. Clinical suspicion should be raised with certain history and physical examination findings. Evidence Acquisition: Scientific and review articles were searched through PubMed (1930-2012) with search terms including stress fractures and 1 of the following: foot ankle, medial malleolus, lateral malleolus, calcaneus, talus, metatarsal, cuboid, cuneiform, sesamoid, or athlete . Study Design: Clinical review. Level of Evidence: Level 5. Results: Stress fractures of the foot and ankle can be divided into low and high risk based upon their propensity to heal without complication. A wide variety of nonoperative strategies are employed based on the duration of symptoms, type of fracture, and patient factors, such as activity type, desire to return to sport, and compliance. Operative management has proven superior in several high-risk types of stress fractures. Evidence on pharmacotherapy and physiologic therapy such as bone stimulators is evolving. Conclusion: A high index of suspicion for stress fractures is appropriate in many high-risk groups of athletes with lower extremity pain. Proper and timely work-up and treatment is successful in returning these athletes to sport in many cases. Low-risk stress fracture generally requires only activity modification while high-risk stress fracture necessitates more aggressive intervention. The specific treatment of these injuries varies with the location of the stress fracture and the goals of the patient.